Long-term dynamics of biomass and modern fishery of atka mackerel Pleurogrammus monopterygius in the Pacific waters of Kamchatka and Kuril Islands - Alexander O. Zolotov; Oleg G. Zolotov; Igor U. Spirin (Известия ТИНРО)
Dynamics of commercial stock for the Kuril-Kamchatka population of atka mackerel is evaluated on the data on size-age structure of its catches and fishery statistics for 1968-2014. Long period of low abundance was observed until the early 1990s, with the minimum stock in 1976-1977 when the spawning biomass was about 24.5. 103 t and commercial one about 29.4. 103 t, then the biomass increased sharply in the 1995-2002, up to 545. 103 t, and decreased in the last decade. However, the recent stock allows to withdraw about 30-50. 103 t of atka mackerel annually. The modern fishery is conducted over vast areas in the Pacific waters of Kamchatka and Kuril Islands, has complicated structure and is based on different functional parts of the population, in connection with biological cycle of this species. The bulk of annual landing is provided by vessels equipped with bottom trawls (on average 86 % in 1997-2014), the rest is landed by pelagic trawls (8 %) and Danish seines (6 %). The main fishing grounds for atka mackerel are located at Kuril Islands where about 70 % of annual catch is landed, the 30 % rest is caught in the bays along the coast of East Kamchatka and on the southeastern shelf of Peninsula.